Power, Community, and Racial Killing in East St. Louis - McLaughlin, M. author. aut Link
XIV, 283 p.
Keywords: Malcolm McLaughlin's work presents a detailed analysis of the East St. Louis race riot in 1917, offering new insights into the construction of white identity and racism. He illuminates the "world of East St Louis", life in its factories and neighborhoods, its popular culture, and City Hall politics, to place the race riot in the context of the city's urban development.